Mid-upper-arm Circumference and Arm-to-height Ratio in Evaluation of Overweight and Obesity in Han Children - Qiang Lu; Rui Wang; Dong-Hui Lou; Chun-Ming Ma; Xiao-Li Liu; Fu-Zai Yin (Elsevier, 2014)
The purposes of this study were: (1) to analyze whether mid-upper-arm circumference (MUAC) could be used to determine overweight and obese children and to propose the optimal cutoffs of MUAC in Han children aged 7-12 years; and (2) to evaluate the feasibility and accuracy of the arm-to-height ratio (AHtR) and propose the optimal cutoffs of AHtR for identifying overweight and obesity. Materials and methods: In 2011, anthropometric measurements were assessed in a cross-sectional, population-based study of 2847 Han children aged 7-12 years. Overweight and obesity were defined according to the 2004 Group of China Obesity Task Force definition. The AHtR was calculated as arm circumference/height. Receiver operating characteristic curve analyses were performed to assess the accuracy of MUAC and AHtR as diagnostic tests for elevated body mass index (BMI; defined as BMI ≥ 85th percentiles). Results: The accuracy levels of MUAC for identifying elevated BMI [as assessed by area under the curve (AUC)] were over 0.85 (AUC: approximately 0.934-0.975) in both genders and across all age groups. The MUAC cutoff values for elevated BMI were calculated to be approximately 18.9-23.4 cm in boys and girls. The accuracy levels of AHtR for identifying elevated BMI (as assessed by AUC) were also over 0.85 (AUC: 0.956 in boys and 0.935 in girls). The AHtR cutoff values for elevated BMI were calculated to be 0.15 in boys and girls. Conclusion: This study demonstrates that MUAC and AHtR are simple, inexpensive, and accurate measurements that may be used to identify overweight and obese Han children. Compared with MUAC, AHtR is a nonage-dependent index with higher applicability to screen for overweight and obese children.